Recent Developments In Chemistry Of 1,3,4-Thiadiazoles - Mahmoud, Mahmoud Refaee; Ismail, Mahmoud Fawzy (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The methods of preparation, structure and biological activities of 1,3,4-thiadiazoles are reported.